Effect of Febuxostat versus Allopurinol on the Glomerular Filtration Rate and Hyperuricemia in Patients with Chronic Kidney Disease - Shankar Prasad Nagaraju; Srinivas Vinayak Shenoy; Indu Rao; Ravindra Attur Prabhu; Dharshan Rangaswamy; Mohan V. Bhojaraja; Vasudeva Guddattu (Saudi Journal of Kidney Diseases and Transplantation, 2023)
Hyperuricemia is a risk factor for the progression of chronic kidney disease (CKD). We compared febuxostat versus allopurinol in the progression of CKD and hyperuricemia in 101 patients with Stage 3–4 CKD treated with febuxostat or allopurinol for at least 6 months for hyperuricemia (>7 mg/dL) between January 2012 and December 2016. Baseline characteristics, serum uric acid (SUA), serum creatinine, and estimated glomerular filtration rate (eGFR) at entry and 6 months were compared. The primary outcome was the decline in eGFR and the secondary outcomes were reductions in SUA and adverse events. Fifty-four were in the febuxostat group and 47 were in the allopurinol group. The baseline characteristics were comparable except for age. The mean dose of febuxostat and allopurinol was 43.70 ± 14.5 mg and 108.51 ± 40 mg, respectively. After 6 months, the median rate of decline in eGFR was 1.2 mL/min/1.73 m2 (IQR: 1.2, 5.5) in the febuxostat group and 3.1 mL/min/1.73 m2 (0.6, 6.2) in the allopurinol group, but this was not statistically significant (P = 0.136). The mean reduction in SUA was significantly better (P = 0.004) in the febuxostat group (3.9 ± 1.7 mg/dL) compared with the allopurinol group (2.1 ± 1.0 mg/dL). Both drugs had no serious adverse events. Febuxostat was better at reducing hyperuricemia than allopurinol, but there was no significant difference in the progression of CKD. Large randomized trials and long-term follow-up are necessary to see whether febuxostat has a favorable effect on the progression of CKD.